1975
DOI: 10.2135/cropsci1975.0011183x001500040032x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Reductase Activity of Grain Sorghum Leaves as Related to Yields of Grain, Dry Matter, and Nitrogen1

Abstract: Eleven grain sorghum (Sorghum bicolor L. Moench) hybrids were grown in the field and growth chamber. Leaf blade samples were assayed by in vitro and in vivo procedures for nitrate reductase activity (NRA) to i)termine NRA of the hybrids, ii) examine relationships between NRA and grain and N yields, and iii) determine whether NRA of growth chamber‐grown plants are indicative of those of field‐grown plants. Among hybrids, differences in yields of grain, dry matter, and grain protein and in in vitro NRA were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…In eukaryotes, reduction of nitrate to nitrite is catalyzed by the molybdenum-containing NR. NR is described as the rate-limiting step of the nitrate assimilation pathway, which eventually influences the growth and organic N status of plants [27,28]. Our data suggested that NO 3 − -N and NH 4 + -N contents and NR activity were decreased by Mn deficiency (Figs.…”
Section: Discussionmentioning
confidence: 58%
“…In eukaryotes, reduction of nitrate to nitrite is catalyzed by the molybdenum-containing NR. NR is described as the rate-limiting step of the nitrate assimilation pathway, which eventually influences the growth and organic N status of plants [27,28]. Our data suggested that NO 3 − -N and NH 4 + -N contents and NR activity were decreased by Mn deficiency (Figs.…”
Section: Discussionmentioning
confidence: 58%
“…However, nitrate reductase activity was positively correlated with N accumulation in other studies with wheat (Eilrich and Hageman 1973;Dalling et al 1975;Vouillot et al 1996), in corn (Deckard et al 1973;Feil et al 1993) and in sorghum (Eeck et al 1975). This lack of consensus on the role of nitrate reductase activity, expressed per unit of fresh tissue, in N uptake appears to preclude the use of this assay to predict the capacity of wheat genotypes to accumulate N. Once plant size was taken into account, the NRA of entire shoot of Vigour 18 was higher than those of Janz for a given NO 3 -treatment and specific plant stage, and total NRA was correlated with root NO 3 -specific absorption rate and plant N uptake.…”
Section: Differences In Physiological Processes and Nitrate Uptakementioning
confidence: 64%
“…It is affected by factors such as plant development stages [28] as well as environmental conditions [29]. We observed that deprivation of Mg 2+ inhibited NR and NiR activities in spinach significantly, which either is due to reduced carbon fixation or low nitrate translocation and subsequently low nitrate availability in spinach or reduced uptake of nitrate by roots or limitations in reducing power.…”
Section: Discussionmentioning
confidence: 79%